A halogen ion-selective phosphorescence turn-on probe based on induction of Pt–Pt interactions. Issue 75 (29th August 2019) - Yang, Jing; Sun, Lili; Hao, Liang; Yang, Gang-Gang; Zou, Zhi-Cong; Cao, Qian; Ji, Liang-Nian; Mao, Zong-Wan
Abstract : A halogen ion induced self-assembly of square-planar platinum complexes has been, for the first time, observed and applied as a turn-on phosphorescent probe for Cl − . Abstract : Square-planar cyclometalated platinum(ii ) complexes have been found to serve as turn-on phosphorescent probes selectively for biological halogen ions. This is based on the halogen ion induced self-assembly of Pt(ii ) compounds in aqueous media, resulting in intermolecular Pt–Pt interaction associated emission.